2011
DOI: 10.2478/v10141-011-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Sport as a Means of Inclusion in Discussions of Sustainable Development for Visually Disabled People

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The association between PA and mental health has been widely investigated in adolescent populations in general Camero, Hobbs, Stringer, Branscum, & Taylor, 2012), but has not been studied among adolescents with visual impairment. All studies from Westernized and non-Westernized countries have included adults and used either a crosssectional design Holbrook, Caputo, Perry, Fuller, & Morgan, 2009;Labudzki & Tasiemski, 2013;Valliant, Bezzubyk, Daley, & Asu, 1985) or a qualitative design (Pereira, Osborne, Cabral, & da Silva, 2011). Hence, population-based studies with prospective designs and including a sample of adolescents are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The association between PA and mental health has been widely investigated in adolescent populations in general Camero, Hobbs, Stringer, Branscum, & Taylor, 2012), but has not been studied among adolescents with visual impairment. All studies from Westernized and non-Westernized countries have included adults and used either a crosssectional design Holbrook, Caputo, Perry, Fuller, & Morgan, 2009;Labudzki & Tasiemski, 2013;Valliant, Bezzubyk, Daley, & Asu, 1985) or a qualitative design (Pereira, Osborne, Cabral, & da Silva, 2011). Hence, population-based studies with prospective designs and including a sample of adolescents are needed.…”
Section: Introductionmentioning
confidence: 99%
“…(3) The findings of this review endorse that participation in sport is beneficial for psychological well-being, indicators of psychological ill-being, and social outcomes in adults. The 152 statements reached were processed into six key categories, namely: policy (29), fundamental conditions (28), key elements (30), soft skills (20), field gaps (31), and best practices (14). Ten keywords were extracted from each of the six categories using the free online program cortical.io.…”
Section: Resultsmentioning
confidence: 99%
“…For example, using keywords in Google Scholar such as disability or impairment, children and youth, sports clubs, sport, or organized sport and inclusion, approximately 13,100 reviewed articles were found in the databases over the last ten years [ 28 ]. Our review found a wide variety of methods for studying the topic of sport inclusion of people with disabilities, using questionnaires [ 12 , 24 , 29 ] and/or structured, semi-structured interviews or narrative inquiry [ 11 , 24 , 25 , 30 ], Moreover, a confirmatory questionnaire was created to assess the involvement in sport, with an analysis based on theoretical foundations such as the social model of disability, the definition of abilities, the nature of social inclusion/exclusion, sources of motivation, the form of social support, the theory of planned behavior, DeLuca’s four conceptions of inclusion [ 31 ], the block model of empowerment, and social field theory [ 8 , 11 , 13 , 24 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between PA and mental health has been widely investigated in adolescent populations in general (Ahn & Fedewa, 2011; Camero, Hobbs, Stringer, Branscum, & Taylor, 2012), but has not been studied among adolescents with visual impairment. All studies from Westernized and non-Westernized countries have included adults and used either a cross-sectional design (Di Cagno et al, 2013; Holbrook, Caputo, Perry, Fuller, & Morgan, 2009; Labudzki & Tasiemski, 2013; Valliant, Bezzubyk, Daley, & Asu, 1985) or a qualitative design (Pereira, Osborne, Cabral, & da Silva, 2011). Hence, population-based studies with prospective designs and including a sample of adolescents are needed.…”
Section: Introductionmentioning
confidence: 99%